1973
DOI: 10.1080/01621459.1973.10481428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Time and Memory Factors on Response in Surveys

Abstract: This articledescribes a simple model of the effects of timeon memory. The model combines the effects of forgetting and telescoping where the event is remembered as occurring more recently than it did. The model is tested on behavior data for which validation information are available. The use of records and of aided recall are shown to have opposite effects on memory errors. Records reduce telescoping effects, but not errors of omission. Aided recall reduces omissions, but does not reduce and may even increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
189
0
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(198 citation statements)
references
References 4 publications
4
189
0
5
Order By: Relevance
“…Some studies have suggested that recollection for the timing of past events is affected by the time elapsed since the event (Janson 1990;Bachman and O'Malley 1981;Sudman and Bradburn 1973). A ''telescoping'' effect occurs when, compared to more recent events, distant events are recalled as having occurred somewhat closer to the time of recall.…”
Section: Limitationsmentioning
confidence: 97%
“…Some studies have suggested that recollection for the timing of past events is affected by the time elapsed since the event (Janson 1990;Bachman and O'Malley 1981;Sudman and Bradburn 1973). A ''telescoping'' effect occurs when, compared to more recent events, distant events are recalled as having occurred somewhat closer to the time of recall.…”
Section: Limitationsmentioning
confidence: 97%
“…Whether or not recall problems occur often depends on the recall period. Underreporting of events is found to increase as time since the event elapses (Sudman and Bradburn 1973;1974). Particularly for the oldest birth cohorts and the earliest periods of calendar time included in the analysis, recall errors may thus affect the quality of retrospectively estimated indicators (Neels 2006;Kreyenfeld et al 2010;Sauer, Ruckdeschel, and Naderi 2012).…”
Section: Item Nonresponse Errormentioning
confidence: 99%
“…Neter (1970) also studied recall errors, telescoping errors, reporting load effects, and conditioning effects in repeated interviewing. Sudman and Bradburn (1973) studied the retrieval of memories of past events by using an exponential model to describe the proportion of events that are reported as a function of the length of duration since the event. Using Weber's law, Sudman and Bradburn evaluated the relative error in the length of the time period reported.…”
Section: Review Of Literaturementioning
confidence: 99%